Increasing Understanding and Perceived Confidence of Nurses Working in an Emergency Department in Assessing Patients at Risk of Violent Behavior. Issue 3 (May 2023) - Inuenwi, Blossom; Lommel, Lisa; Peter, Swapna B.; Carley, Annette
Abstract : Purpose: The aims of this quality improvement project were to improve understanding and perceived confidence in using a tool that assesses patients at risk of violence. Project Description: The Brøset Violence Checklist is valid at assessing patients at risk of violence. Participants were given access to an e-learning module that demonstrated how to use the tool. Improvement in understanding and perceived confidence in using the tool were assessed preintervention and postintervention via an investigator-developed survey. Analysis of the data was conducted using descriptive statistics, and open-ended survey responses were analyzed using content analysis. Outcome: Participants did not demonstrate an increase in understanding and perceived confidence after introduction of the e-learning module. Nurses reported that the Brøset Violence Checklist was easy to use, clear, reliable, and accurate and could be used to standardize assessments of at-risk patients. Conclusion: Emergency department nursing staff were educated in use of a risk assessment tool for identifying patients at risk of violence. This supported the implementation and integration of the tool into emergency department workflow.